THE DIFFERENTIATION OF SHEEP BREED BASED ON THE BODY MEASUREMENTS - Handiwirawan, E.; Noor, R.R.; Sumantri, C.; Subandriyo, S. (Diponegoro University, 2011)
This research was carried out to make a difference and to predict genetic distance some sheep thatare genetically related to each other based on the body size measurements. Nineteen bodies size of 323sheeps of five sheep breeds; namely Barbados Black Belly Cross (BC), Garut Local (GL), GarutComposite (GC), Sumatra Composite (SC) and St. Croix Cross (SCC) were measured. Analysis ofvariance and canonical discriminant analysis, Mahalanobis distance, plotting canonical and dendogramwere performed using PROC GLM, PROC CANDISC, PROC CLUSTER and PROC TREE of SASsoftware ver. 9.0. Index Length, Width Slope, Depth Slope, Balance and Cumulative Index of GC sheepwere significantly higher than the four other breeds. Canonical discriminant analysis successfully coulddifferentiate among the five sheep breeds. All five breed were divided into two groups: the first groupconsisted of SCC, SC and BC; and the second group consisted of the GL and GC. The results of geneticdistance estimation showed that the SCC had a value of sheep genetic distance closest to SC (10.83) andBC (27.98), while GL had the closest distance to GC (66.60). The tail width, horn base circumference,horn length (canonical 1) and variable length of the tail and body length (canonical 2) were the breeddifferentiation variable in this study.